Ecological implications of push-net fisheries on demersal fish biodiversity and bycatch in Banyuasin coastal waters, Indonesia - HELFA SEPTINAR; FAUZIYAH FAUZIYAH; FITRI AGUSTRIANI; AMANDA ASTRI PRATIWI FEBRIANTI; ELLIS NURJULIASTI NINGSIH; ISNAINI ISNAINI; DADE JUBAEDAH; BAKRI BAKRI; ROZIRWAN ROZIRWAN (Society for Indonesian Biodiversity, 2026)
Abstract. Septinar H, Fauziyah, Agustriani F, Febrianti AAP, Ningsih EN, Isnaini, Jubaedah D, Bakri, Rozirwan. 2026. Ecological implications of push-net fisheries on demersal fish biodiversity and bycatch in Banyuasin coastal waters, Indonesia. Biodiversitas 27 (2): d270224. https://doi.org/10.13057/biodiv/d270224. Push-net fisheries are widely practiced in Indonesian coastal waters but often generate substantial bycatch, posing ecological risks to demersal fish communities and near-threatened species. This study examined the catch composition, species diversity, and ecological linkages of push-net fisheries in the Banyuasin coastal waters, South Sumatra, and assessed the environmental drivers influencing assemblage structure. Seven fishing trips comprising 33 hauls yielded 4,157 individuals (115.87 kg total biomass). Data were analyzed using ecological indices, including Relative Abundance (RA), Occurrence Frequency (Fi), Shannon-Wiener Diversity (H’), Pielou’s Evenness (E), Simpson’s Dominance (D), and the standardized Morisita Index (Ip). The main catch (Metapenaeus monoceros, Penaeus merguiensis, Mierspenaeopsis sculptilis, Harpiosquilla raphidea, and Macrobrachium rosenbergii) contributed 51.08% (59.19 kg) of the total catch, while bycatch and discards accounted for 40.33% (46.73 kg) and 8.59% (9.95 kg), respectively. The main catch was dominated by M. monoceros (RA = 35.55%, Fi = 100%) and P. merguiensis (RA = 21.22%, Fi = 100%), defining the core shrimp assemblage. Among the 20 bycatch species identified, Johnius carouna was the most dominant (RA = 21.65%, Fi = 85.71%), while Clibanarius spp. and Lagocephalus spadiceus dominated the discard fraction. Shannon-Wiener diversity (H’ = 0.61-2.08) indicated low to moderate diversity, while evenness (E = 0.17-0.58) and dominance (D = 0.17-0.76) reflected uneven community structure and moderate dominance by a few taxa. The standardized Morisita index (Ip = 0.55-0.87) confirmed clustered distributions. Principal Component Analysis (PCA) explained 68.16% of total variance (F1 = 43.48%, F2 = 24.68%), highlighting strong multivariate associations between environmental variables (dissolved oxygen, temperature, and salinity) and bycatch variation across sampling sites. These findings highlight the influence of environmental variability and fishing pressure on species assemblages and emphasize the need for adaptive, ecosystem-based management to mitigate bycatch and sustain tropical coastal fisheries.